Additive Manufacturing of 3D Luminescent ZrO2:Eu3+ Architectures (Advanced Optical Materials 12/2022). Issue 12 (20th June 2022) - Winczewski, Jędrzej; Herrera, Manuel; Cabriel, Clément; Izeddin, Ignacio; Gabel, Stefan; Merle, Benoit; Susarrey Arce, Arturo; Gardeniers, Han
Abstract : In article number 2102758, Jedrzej Winczewski, Arturo Susarrey Arce, Han Gardeniers and co‐workers present additively‐manufactured 3D luminescent microstructures emitting light in the visible range. The 3D europium‐doped zirconia (ZrO2 :Eu 3+ ) architectures are fabricated via two‐photon lithography using custom‐made photoresin. The orange‐red emission of ZrO2 :Eu 3+ microstructures of sub‐micrometer feature size definition is demonstrated using fluorescence microscopy and investigated in detail with cathodoluminescence. The presented structuring technology provides a new platform for developing 3D luminescent microdevices and optimizing phosphor‐based light emitters further.